Analisis Cerpen “Manusia Kelelawar” Karya Damhuri Muhammad melalui Pendekatan Struktural dan Moral - Putri, Aisyah Meilani; Abdurahman, Abdurahman (TSAQOFAH, 2026)
A study of the short story Manusia Kelelawar by Damhuri Muhammad is important to reveal the relationship between the structural elements and the moral values constructed in the literary text. This study aims to describe the structural elements, which include theme, plot, character and characterization, setting, and point of view, while also identifying the moral values contained in the short story. This study employed a descriptive qualitative method with text analysis techniques, with the short story as the primary data source. The results show that, structurally, this short story presents a complex psychological conflict as a result of the loss and trauma experienced by the main character. Meanwhile, through the moral approach, values were found that emphasize the importance of not isolating oneself from the environment, maintaining emotional resilience, and drawing closer to God in facing life’s problems. These findings indicate that literary works not only represent an aesthetic structure through their intrinsic elements, but also contain moral messages that are relevant to readers. Thus, the short story Manusia Kelelawar can be understood as a work that presents psychological reflection as well as a means of moral learning.